Caribbean Agricultural Information Service (CAIS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Caribbean Agricultural Information Service (CAIS)supports the development of national networks and provides technical and marketing information for the agricultural sector.